Extracting DNA from soil or directly from isolated nematodes indicate dissimilar community structure for Europe-wide forest soils - Donhauser Jonathan; Briones Maria J.I.; Mikola Juha; Jones Davey L.; Eder Reinhard; Filser Juliane; Frossard Aline; Krogh Paul Henning; Sousa José Paulo; Cortet Jérome; Desie Ellen; Domene Xavier; et al. (Elsevier Ltd, 2025)
Nematodes are numerous in soils and play a crucial role in soil food-webs. DNA metabarcoding offers a time-effective alternative to morphology-based assessments of nematode diversity. However, it is unclear how different DNA extraction methods prior to metabarcoding could affect community analysis. We used soils with woody vegetation from a European latitudinal gradient (29 sites, 39 to 79°N, ∼4500 km, covering six biomes) to systematically evaluate the effect of two sources of nematode DNA either directly extracted from soils vs. extracted from nematodes previously isolated from soils hypothesizing that the DNA source material may produce different diversities, community structures and abundances of feeding types. Nematode-sample DNA exhibited a higher richness, while no difference in Shannon diversity was found between the approaches. The DNA sources also created significantly different community structures, with greater differences observed across soil-extracted DNA than nematode-sample DNA. The most overrepresented species in nematode-sample DNA were Heterocephalobus elongatus, Eucephalobus striatus and Hexatylus sp., whereas Phasmarhabditis sp. and Eumonhystera filiformis were overrepresented in soil-extracted DNA. Read abundances of feeding types significantly differed between the DNA sources and across sites, with a significant effect of biome on both ecto- and endoparasitic herbivores in soil-extracted DNA and for ectoparasitic herbivores only in nematode-sample DNA. Collectively, our data suggest that choice of the DNA source material may lead to different patterns of nematode community composition across space and environmental conditions. Improving the sensitivity of the soil-extracted DNA method by developing protocols using larger amounts of soil and designing nematode-specific primers will make this approach an efficient screening tool to analyse nematode diversity and community structure complementing the labour-intensive isolation of intact nematodes from soils (nematode-sample DNA).